Design and development of novel biomaterials for cardiac tissue engineering - Baptista, Hélder Duarte de Magalhães Oliveira (2022)
Cardiovascular diseases remain the leading cause of death worldwide. Myocardial infarction is among them, usually leading to heart failure due to the inability of the cardiomyocytes to regenerate. It is thus imperative to develop strategies in order to assist these patients. Tissue engineering is one of the most studied fields, focusing on the development of suitable structures, such as porous structures and films, to replace the damaged tissue while regeneration occurs. However, the selection of an appropriate biomaterial may be difficult, since it must meet the properties, such as physical, mechanical, degradation and biocompatibility, similar to the tissue to be replaced. In this study, poly(L-lactic acid) (PLLA) and diphenylalanine (FF), were used, due to their promising piezoelectric and biocompatibility properties, to produce a film consisting of three-layers (PLLA/FF/PLLA) spin coated on top of each other. Piezocoefficient, d33, was found to be ~6-7 pm/V, and mainly derived from the FF layer. Degradation tests showed preservation of the FF layer after deposition of the last layer, PLLA. Porous structures were also developed and consisted of chitosan-silk with different ratios - 2:8, 1:1 and 8:2. A porous structure was observed and the percentage of pores was found to be 66.3, 80.3 e 55.7%, and the Young’s Modulus was 46, 98 and 163 kPa, respectively. It was found that the 8:2 ratio Young’s Modulus was very close to the ~10-20 kPa for cardiac tissue. Degradation of the porous structures after three weeks resulted in the conservation of 90 and 80% of their weight, for the 2:8 and 8:2 ratios, however their porous structure was lost only after 1 week. This work showed promising results, especially regarding the piezoresponse of the films and porosity of the porous structures. Piezoelectricity should provide the cardiomyocytes with electric stimulation while porosity facilitates their migration, both helping during tissue regeneration.